2020
DOI: 10.1021/acs.energyfuels.0c00587
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Ash-Fusion Characteristics of Livestock Manure and Low-Rank Coals

Abstract: Large amounts of livestock manure are produced annually, and cogasification offers a promising method for large-scale and clean use of manure. To investigate the ash-fusion characteristics (AFC) of livestock manure and coal, and their variation mechanisms, the AFCs of two coals (Yima long-flame coal and Husheng lignite), two manures (cattle manure (CM), and swine manure (SM)), and their mixtures were explored. An increase in the ash mass ratio of the CM or SM increased the sintering temperature (T s) of two mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This could hinder the deposition of ash particles and therefore be the reason for a comparably thinner average layer formation [15]. At the interface of the deposited ash particles and the bed particle, Ca 5 P 2 SiO 12 was calculated to form, which agrees with the previously suggested formation of silicophosphates occurring when different P-rich fuels were thermally converted [9,[49][50].…”
Section: Tablesupporting
confidence: 81%
“…This could hinder the deposition of ash particles and therefore be the reason for a comparably thinner average layer formation [15]. At the interface of the deposited ash particles and the bed particle, Ca 5 P 2 SiO 12 was calculated to form, which agrees with the previously suggested formation of silicophosphates occurring when different P-rich fuels were thermally converted [9,[49][50].…”
Section: Tablesupporting
confidence: 81%
“…If ash content could be reduced to less than 10%, then potentially these low-grade Colombian coals could be used as metallurgical coals, 54 and command a much higher price in the global coal market. 8 Ash fusion ovens (AFO) are usually used to investigate the slagging and fouling characteristics of fuels, 59 but this study has identified a novel use for AFO to analyze coal swelling. Lumps (<6 mm) of Cundinamarca and Antioquia were placed in an AFO and heated to 900 °C in air and recorded using an externally mounted camera.…”
Section: Resultsmentioning
confidence: 99%
“…Ash fusion ovens (AFO) are usually used to investigate the slagging and fouling characteristics of fuels, but this study has identified a novel use for AFO to analyze coal swelling. Lumps (<6 mm) of Cundinamarca and Antioquia were placed in an AFO and heated to 900 °C in air and recorded using an externally mounted camera …”
Section: Resultsmentioning
confidence: 99%
“…Since no systematic compilation of phosphorus-rich biomass is available in the literature, the data for 96 different biomasses from studies relating to thermal conversion are compiled in this review (refs , , , , , , , , , , ). The amount of phosphorus in these biomasses is shown in Figure .…”
Section: Phosphorus In Biomassmentioning
confidence: 99%